Aspects of labour planning - Heinz Werner (Intereconomics, 1973)
According to the latest census of April 1, 1971, India had a total population of about 547 million, of which 184 million were the potential labour force (i.e., all employed persons and all the unemployed, taken together). As the population growth is still accelerating, it is foreseen that the country's population will reach about 695 million by 1981 which means that new jobs should be found every year for six million potential workers.
Keywords: 330; India